Assessment of decreased left ventricular longitudinal deformation in asymptomatic patients with organic mitral regurgitation and preserved ejection fraction using tissue‐tracking mitral annular displacement by speckle‐tracking echocardiography - Teraguchi, Ikuko; Hozumi, Takeshi; Takemoto, Kazushi; Ota, Shingo; Kashiwagi, Manabu; Shimamura, Kunihiro; Shiono, Yasutsugu; Kuroi, Akio; Yamano, Takashi; Yamaguchi, Tomoyuki; Matsuo, Yoshiki; Ino, Yasushi; et al. (Echocardiography, 2019)
Background: Application of speckle‐tracking echocardiography (STE) provides rapid assessment of tissue‐tracking mitral annular displacement (TMAD). We investigated the value of TMAD for the assessment of decreased LV longitudinal deformation in asymptomatic patients with severe or moderate‐to‐severe mitral regurgitation (MR) and preserved LV ejection fraction (LVEF). Methods: We retrospectively studied 50 patients with severe or moderate‐to‐severe organic MR and preserved LVEF (>60%) in whom global longitudinal strain (GLS) was successfully measured by STE. TMAD was quickly assessed in the apical four‐chamber view using STE. We calculated the percentage of TMAD to LV length from the midpoint of mitral annulus to the apex at end‐diastolic (%TMAD). The study population was divided into two groups: decreased GLS patients (>−20%; Group A) and preserved GLS patients (≤−20%; Group B). We examined whether %TMAD could be used as a diagnostic factor of decreased GLS. Results: %TMAD was significantly lower in Group A than Group B (12.5 ± 0.5 vs 16.8 ± 2.2, P < 0.0001). By univariate logistic regression analysis, %TMAD was a diagnostic factor of decreased GLS. By multiple regression analysis, %TMAD remained an independent diagnostic factor of decreased GLS (Odds ratio [OR] = 4.21, 95% confidence interval [CI] = 1.34–28.94, P < 0.0001). A cutoff value of %TMAD <14.6 had a sensitivity of 94% and specificity of 94% for the presence of decreased GLS. Conclusions: Tissue‐tracking mitral annular displacement is useful in the assessment of decreased LV longitudinal deformation in asymptomatic patients with severe or moderate‐to‐severe MR and preserved LVEF.